Public interest considerations under the Competition Act No. 89 of 1998 and the effect on Foreign Direct Investments (FDIs) in South Africa - Van Heerden, C.M. (Corlia) (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.